Anterior Mediastinal Mass: A Rare Presentation of Tuberculosis - Gopi C. Khilnani; Neetu Jain; Vijay Hadda; Sudheer K. Arava (Journal of Tropical Medicine)
We report a case of a 14-year-boy who presented to us with a low-grade fever with evening rise for 9 months. Along with this, the patient also reported a reduction in his appetite and body weight. He had a mild dry cough but no respiratory symptoms otherwise. There was no other localization for fever on history. He received antitubercular therapy, based on abnormal chest radiograph. However, there was no relief in his symptoms. General physical examination revealed mild fever. Systemic examination was unremarkable. Blood investigations done for fever were noncontributory. Computed tomographic (CT) scan of the chest revealed a mediastinal mass compressing the trachea. The possibilities of lymphoma or germ cell tumour were considered. A biopsy from the mass under CT guidance was performed. The histopathology revealed multiple epithelioid cell granulomas with necrosis, and the diagnosis of tuberculosis was made. The clinical course of this patient and the relevant literature is presented in this paper.